The Palestine Issue: Why The United Nations Refused to Accept as A United Nations Member and As a Nation State? - Mohd. Noor Mat Yazid; Sharija Che Shaari (Fakulti Pengajian Islam, Universiti Malaysia Sabah, 2023)
This paper explores the Palestine issue from the international law and international politics. Why the United Nations Organization refused to accept Palestine as a United Nations Member and recognized Palestine as a nation state in the international political structure? The Article 4(1) and Article 4(2) of the United Nations Charter would be applied in discussing of the Palestine issue. Article 4(1) stated that “ Membership in the United Nations is open to all other peace-loving states which accept the obligations contained in the present Charter and, in the judgement of the Organization, are able and willing to carry out these obligation,” Article 4(2) stated that, “The admission of any such state to membership in the United Nations will be affected by a decision of the General Assembly upon the recommendation of the Security Council.” The main problem that embroils Palestine to be recognized as a state and admitted as a member in the United Nations due to the recommendation from Security Council as stated in the Article 4(2) of the United Nations Charter. The United States always objects the Resolutions passed by the General Assembly. The United States uses the veto power to veto the Palestine admission. This study concludes that the failure of the Palestine to be admitted as a United Nations member and recognized as a state was due to the geo-political factors.